24 the editing process - Gallant, Michael; Bilson, Bruce; Academy of Television Arts & Sciences Foundation; Gallant Entertainment; TMW Media Group; First Light Video Publishing (Venice, CA : TMW Media Group Inc., 2005)
Examines the technical editing process for the television program'24'
Features: outtakes from television show, interviews with actors and technical crew, interviews with editors and script supervisors guild members, suggested curriculum material for television production courses
Title from cover
Music by Ray Colcord ; director of photography, Christopher Gallo ; edited by Judd Maslansky ; associate producer, Lynne gross
Host: Kiefer Sutherland
Keywords: Television -- Production and direction; Television scripts -- Editing